Shame and attachment loss: the practical work of reparative therapy - Nicolosi, Joseph (IVP Academic, 2009)
Introduction -- Psychodynamics of homosexuality -- Overview : advances in reparative therapy -- Family dynamics -- Homosexuality as a shame-based symptom -- Homosexuality as a repetition compulsion -- Homosexuality as a reparative drive -- Treatment : affect-focused therapy -- The primacy of affect -- The body -- Reparative body work : the concept of the two-triangle sequence -- Reparative body work : working the two-triangle sequence -- The double bind -- The double loop -- From double bind to double loop -- The scenario preceding homosexual enactment -- Working through the scenario preceding homosexual enactment -- Journaling -- Counseling teenagers -- Male friendships -- Relationships with women -- Grief work -- The role of grief work in reparative therapy -- Approaching the core injury -- Defenses against grief -- Homosexual enactment as an opportunity for grief work -- Resolution of grief : a life without illusions and distortions